Solve this equation using the quadratic formula:  (2x-3)^2 - 14 = 2x(x-7)

1 Answer | Add Yours

crmhaske's profile pic

crmhaske | College Teacher | (Level 3) Associate Educator

Posted on

First, we need to simpify the equation to standard form `(ax^2+bx+c)` :

Expand the squared term:


Next expand the multiplication:


Finally, move all terms to the left side and collect like terms:



We can now solve for the roots of this equation using the quadratic formula:

`x=(-b+-sqrt(b^2-4ac)) /(2a)`

a=2; b=2; c=-5

`x=(-2+-sqrt(2^2-4(2)(-5))) /(2(2))`


`x_1=(-2+sqrt(44))/4 =1.16`  


Graph of the function:

We’ve answered 320,049 questions. We can answer yours, too.

Ask a question